Impact of SARS-CoV-2 on healthcare and essential workers: A longitudinal study of PROMIS-29 outcomes. - Jocelyn Dorney; Imtiaz Ebna Mannan; Caitlin Malicki; Lauren E Wisk; Joann Elmore; Kelli N O'Laughlin; Dana Morse; Kristyn Gatling; Michael Gottlieb; Michelle Santangelo; Michelle L'Hommedieu; Nicole L Gentile; et al. (PLoS ONE, 2025)
Importance The mandatory service of essential workers during the COVID-19 pandemic was associated with high job stress, increased SARS-CoV-2 exposure, and limited time for recovery following infection. Understanding outcomes for frontline workers can inform planning for future pandemics. Objective To compare patient-reported outcomes by employment type and SARS-CoV-2 status. Design Data from the INSPIRE registry, which enrolled COVID-positive and COVID-negative adults between 12/7/2020-8/29/2022 was analyzed. Patient-reported outcomes were collected quarterly over 18 months. Setting Participants were recruited across eight US sites. Participants Employed INSPIRE participants who completed a short (3-month) and long-term (12-18 month) survey. Exposure SARS-CoV-2 index status and employment type (essential healthcare worker [HCW], essential non-HCW, and non-essential worker ["general worker"]). Main outcomes and measures PROMIS-29 (mental and physical health summary) and PROMIS Cognitive SF-CF 8a (cognitive function) scores were assessed at baseline, short-term (3-months), and long-term (12-18 months) timepoints using GEE modeling. Results Of the 1,463 participants: 53.5% were essential workers (51.4% HCWs, 48.6% non-HCWs) and 46.5% were general workers. Most associations between outcomes and employment type became non-significant after adjusting for sociodemographics, comorbidities, COVID-19 vaccination, and SARS-CoV-2 variant period. However, among COVID-negative participants, essential HCWs had higher cognitive scores at baseline (β: 3.91, 95% CI [1.32, 6.50]), short term: (β: 3.49, 95% CI: [0.80, 6.18]) and long-term: (β: 3.72, 95% CI: [0.98, 6.46]) compared to general workers. Among COVID-positive participants, essential non-HCWs had significantly worse long-term physical health summary scores (β:-1.22, 95% CI: [-2.35, -0.09]) compared to general workers. Conclusions and relevance Differences in outcomes by worker status were largely explained by baseline characteristics. However, compared to general workers, essential HCW status had higher cognitive function in the absence of SARS-CoV-2 infection at all timepoints, while essential non-HCWs were most vulnerable to poor recovery in long-term physical health following SARS-CoV-2 infection. Preparation efforts for future pandemics may consider enhanced protection and post-infection resources for frontline workers.